Lewis Clarke and the "Color" of Disability: The Past and Future of Black Disability Studies - Franzino, Jean (Disability Studies Quarterly, 2016)
This article analyzes Lewis Clarke's 1845 slave narrative, the Narrative of the Sufferings of Lewis Clarke, for what it can offer contemporary theorizing at the intersection of disability and race. Clarke's text, I suggest, "crips" the genre of the slave narrative, replacing abolitionist spectacle with the knowledge gained from a number of temporary or otherwise ambiguous disability positions. In doing so, Clarke's Narrative both expands the parameters of disability as often conceived within disability studies and offers a reconfiguration of the meaning of disability for critical race studies.